Cloud Computing Privacy Security Risk Analysis and Evaluation - Zhang, Qiujin; Jiang, Rong; Li, Tong; Ma, Zifei; Yang, Ming; Yang, Juan (Recent Patents on Computer Science, 2018)
Background: The most important question about the application and development of cloud computing is the privacy risk, as it has become the key factor for users in selecting cloud services. In order to have a better understanding of the privacy risk, resolve or make it controllable in an acceptable range, risk assessment is very necessary. However, specialized research on the assessment has not yet been found. Methods: This paper has used Information Entropy Theory and Fuzzy Set Theory to evaluate cloud computing privacy security risk. Results: This paper analyzes the research actuality of cloud computing privacy security and combs a number of cloud computing privacy security risks on the basis of digging deep into the characteristics of cloud computing and previous studies, thus further establishing an evaluation index system for privacy risk initiatively. Then, the entropy weight theory and fuzzy set theory are used to establish a fusion of multiple factors of the assessment model. Conclusion: A practical case is given to prove the feasibility, rationality and effectiveness of the evaluation method.
Keywords: entropy weight theory